Preschool Children with ADHD - J Gordon Millichap (Pediatric Neurology Briefs)
Differences in behavioral, social, and school functioning of 58 preschool-age (3 -5 years) children with attention deficit/hyperactivity disorder and 36 normal controls were examined at Lehigh University, Bethlehem, PA.